2022
DOI: 10.28985/1221.jsc.09
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heart Rate Variability and Simulated Cycling Time Trial Performance

Abstract: The aim of this study was to determine if an abnormal HRV status would have negative effects on simulated individual time trial (ITT) performance in recreational cyclists. Recreational male (n=23, 42.8±8.3 years, 78.0±11.0 kg) and female (n=2, 37.0±6.8 years, 68.0±4.4 kg) cyclists completed simulated indoor 40-minute ITTs (40TT) over ten weeks. Participants were asked to complete simulated 40TTs under two HRV conditions: HRV normal values and HRV abnormal values. Participants recorded daily morning HRV reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The observed acute decrease in HRV can be attributed to pre-performance anxiety or stress response as previous research has demonstrated an anticipatory response to stressful tasks, meaningful competitions and high-intensity training sessions decreases HRV ( 34 36 ). The performance impact of HRV reductions are equivocal, and could be attributed to the level of athlete and/or the importance of the forthcoming performance bout ( 37 39 ). As such, these acute changes can be seen as expected or beneficial, as increases in sympathetic activity facilitate increases in norepinephrine, epinephrine ( 36 ), bioenergetic pathways ( 40 , 41 ), and neurological processes (i.e., reaction time) ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed acute decrease in HRV can be attributed to pre-performance anxiety or stress response as previous research has demonstrated an anticipatory response to stressful tasks, meaningful competitions and high-intensity training sessions decreases HRV ( 34 36 ). The performance impact of HRV reductions are equivocal, and could be attributed to the level of athlete and/or the importance of the forthcoming performance bout ( 37 39 ). As such, these acute changes can be seen as expected or beneficial, as increases in sympathetic activity facilitate increases in norepinephrine, epinephrine ( 36 ), bioenergetic pathways ( 40 , 41 ), and neurological processes (i.e., reaction time) ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic training may lead to increased HRV in athletes, especially where training includes a strong aerobic component as is common practice among endurance athletes [12,24]. However, acute reductions in daily HRV have been observed in response to heavy training [63][64][65], and days with decreased morning HRV may indicate a reduced performance ability [66]. Athletes with overtraining syndrome have been shown to exhibit reduced HRV compared to healthy, trained athletes [15].…”
Section: Overall Training Loadmentioning
confidence: 99%
“…The concept of ecological validity, or how laboratory-based assessments may, or may not, relate to real-world performance, is so critical but often assumed. We recently tested this convergence by asking cyclists to remotely complete six 40-km time trials, using their personal equipment, while tracking training load, heart rate variability, nutrition, and psychological makers ( 2 ). In addition, we used remote data collection to track competitive youth rowers’ response to long-haul travel ( 3 ) and from an applied perspective, their pretraining heart rate variability across a season ( 4 ).…”
mentioning
confidence: 99%